Development and Validation of RP – HPLC Method for the estimation of Oxyclozanide in Pure and Pharmaceutical formulation - Anusha.G (International Journal of Pharmacy and Analytical Research, 2014)
A simple, fast, precise, selective and accurate RP-HPLC method was developed and validated for the simultaneous determination of oxyclozanide from pharmaceutical formulation. Chromatographic separation was achieved gradient on a YMC c18 column (250 x 4.6 mm, 5 µ particle size) using a mobile phase acetonitrile and water in the ratio of 80:20.the flow rate was 1.0ml / min and effluent was detected at 300nm.the retention time of oxyclozanide was found to be 1.89min. Linearity was observed in the concentration range of 10 -100µg / ml .The method was validated according to ICH guidelines with respect to specificity, linearity, accuracy, precision and robustness. The method developed can be used for the routine analysis of oxyclozanide.